Porosity Prediction from Seismic Inversion for Yamama Formation in (Abu-Amoud) Oil Field in Southern of Iraq - Al-Ridha, Nawal Abed; Rasheed, Mazin (Iraqi Journal of Science, 2018)
The study is an attempt to predict reservoir characterization by improving the estimation of petro-physical properties (porosity), through integration of wells information and 3D seismic data in early cretaceous carbonate reservoir Yamama Formation of (Abu-Amoud) field in southern part of Iraq. Seismic inversion (MBI) was used on post- stack 3 dimensions seismic data to estimate the values of P-acoustic impedance of which the distribution of porosity values was estimated through Yamama Formation in the study area. EMERGE module on the Hampson Russel software was applied to create a relationship between inverted seismic data and well data at well location to construct a perception about the distribution of porosity on the level of all units of Yamama reservoir. Instantaneous frequency attribute is used to confirm the distribution of low value of acoustic impedance, which in turn indicates the location of high porosity values.